Pengoperasian dan Perawatan PLTMH pada Pembangkit Listrik Mikro Hidro (PLTMH) di Sungai Batang Geringging Kota Padang - Fajri Dwi Putra; Nota Effiandi; Desmarita Leni (Politeknik Negeri Padang, 2017)
Water turbine is a tool to convert the potential energy of water into mechanical energy, this mechanical energy is then converted into electrical energy by a generator. Crossflow turbines are radial, small pressurized turbines with tangential injection from fan rotation with a horizontal shaft. The flow of water flows through the pipe entrance, and is arranged by a propeller and into the turbine fan rotation. After the water passes through the turbine fan rotation, the water is at the opposite fan rotation, thus providing additional efficiency. Finally, water flows from the casing either freely or through a tube under the turbine so that it rotates and turns the generator so it can produce electricity. Maintenance of PLTMH is carried out namely preventive maintenance such as; cleaning, lubrication and periodic checks. Maintenance corrections are carried out with the aim of being able to maintain the PLTMH component. Predictive maintenance of a treatment carried out in accordance with the conditions of the PLTMH and predicting damage that will occur in PLTMH